Optimalisasi Penegakan Hukum Pidana terhadap Tindak Pidana Pencucian Uang dengan Modus Jual Beli Rekening Bank: (Studi Putusan Pengadilan Negeri Jakarta Utara Nomor 1080/Pid.Sus/2019/PN. Jkt.Utr dan Putusan Pengadilan Negeri Jakarta Utara Nomor 1131/Pid.Sus/2019/PN. Jkt.Utr) - Pane, Lorita Tupaida; Sunarmi, Sunarmi; Mulyadi, Mahmud; Andriati, Syarifah Lisa (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The increase in diversity and complexity of crimes, including the practice of buying and selling bank accounts, is becoming more rampant through direct transactions and e-commerce platforms such as Tokopedia, Lazada, Shopee, and OLX. This illegal practice not only harms legitimate account holders but also negatively impacts society and the state. Bank accounts that are bought and sold are often used to hold funds from crimes such as fraud, drug trafficking, terrorism, online gambling, and other offenses. This study aims to examine the correlation between the practice of buying and selling bank accounts and money laundering crimes, assess the effectiveness of criminal law enforcement through various court decisions, and explore ways to optimize criminal law enforcement against this modus operandi. The research method employs a normative juridical approach supported by empirical data, as well as analysis of primary, secondary, and tertiary legal materials through library and field research. The results show a strong correlation between the practice of buying and selling bank accounts and money laundering crimes as regulated in Law No. 8 of 2010. Law enforcement is still not optimal, as seen from the disparity in the decisions of the North Jakarta District Court Numbers 1080/Pid.Sus/2019/PN. JKT.UTR and 1131/Pid.Sus/2019/PN. JKT.UTR. Optimizing law enforcement can be achieved by enhancing the roles of investigators, public prosecutors, and judges, as well as strengthening regulations and sanctions against negligent banks. This study emphasizes the importance of a good legal system, cooperation between PPATK and law enforcement agencies, and the application of strict sanctions to prevent the misuse of bank accounts and protect the integrity of the financial system.